Perbedaan Tingkat Konsumsi Energi, Protein, Vitamin A Dan Perilaku Kadarzi ada Anak Balita Stunting Dan Non Stunting Di Desa Kopen Kecamatan Teras Kabupaten Boyolali - PRAKOSO, Bayu Adi; , Susi Dyah Puspowati, SP., M.Si; , Pramudya Kurnia, STP, M.Agr (2015)
Background: Toddlers are our future successor, toddlers also determine the future of the nation. Nutritional problems one of which is a state of stunting short body that is -2SD below the median. Factors affecting the nutritional status is the intake of energy, protein, vitamins A and KADARZI ( conscious family nutrition ). Objective: To identify differences in the level of consumption of energy, protein, vitamins A and KADARZI ( conscious family nutrition ). in stunted and non-stunted children under five Methods: This study used observational method with cross sectional approach. Total sample of 84 children under five. Nutritional status data obtained with the height measurement. Food intake data was obtained through a 24-hour recall. KADARZI ( conscious family nutrition ). data obtained by administering a questionnaire. The statistical test used was the independent test T Test and Test Wilcoxom. Results: Energy consumption is highest in children under five are stunted light energy consumption is 40.5%. whereas the non-stunted children under five highest normal consumption is 76.2%. Highest level of protein intake in infants stunting is normal energy consumption is 57.1% lower than non-stunted children under five highest normal consumption is 66.7%. The level of vitamin A consumption is highest in children under five are stunted normal consumption of vitamin A which is 64.3% higher than non-stunted children under five highest normal consumption is 40.5% . Level KADARZI ( conscious family nutrition ).Good Behavior in children under five years of stunting was 66.6% lwer of stunting children under five years is 83%. The result kolelasi between energy test p = 0.001, p = 0.000 protein, vitamin A p = 0.000 and p = 0.018 KADARZI ( conscious family nutrition ). in children under five stunted and non-stunted. Conclusion: There is a difference in the level of consumption of energy, protein, vitamins A and KADARZI ( conscious family nutrition ). in children under five stunted and non-stunted in Village Teras Kopen District of Boyolali.